2023
DOI: 10.1785/0220220383
|View full text |Cite
|
Sign up to set email alerts
|

2022 Mw 6.6 Luding, China, Earthquake: A Strong Continental Event Illuminating the Moxi Seismic Gap

Abstract: On 5 September 2022, an Mw 6.6 strike-slip earthquake occurred in Luding, Sichuan, China. It illuminates the seismic gap on the southern end of Xianshuihe fault zone, that is Moxi segment, and is the most damaging earthquake in Chinese Mainland since 2014. In this article, we use multiple seismological methods to analyze the basic characteristics of the Luding earthquake, including its source parameters, rupture process, aftershock distribution, and further discuss its implications on preseismic fault behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Following the strategies of Ji et al (2002), we simultaneously invert for the rise time, rupture velocity, fault slip, and rake angle associated with the 2022 Luding earthquake using the simulated annealing method. Based on the relocated aftershocks (Figure 2; An et al, 2022;L. Zhang, Zhou, et al, 2022), the strike and dip are set as 163° and 80°, respectively (L. Zhang, Zhou, et al, 2022).…”
Section: Model Configurationmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the strategies of Ji et al (2002), we simultaneously invert for the rise time, rupture velocity, fault slip, and rake angle associated with the 2022 Luding earthquake using the simulated annealing method. Based on the relocated aftershocks (Figure 2; An et al, 2022;L. Zhang, Zhou, et al, 2022), the strike and dip are set as 163° and 80°, respectively (L. Zhang, Zhou, et al, 2022).…”
Section: Model Configurationmentioning
confidence: 99%
“…Based on the relocated aftershocks (Figure 2; An et al, 2022;L. Zhang, Zhou, et al, 2022), the strike and dip are set as 163° and 80°, respectively (L. Zhang, Zhou, et al, 2022). Previous studies suggested that the rupture initiation point controls the rupture extent of earthquakes due to the heterogeneous strength and stress on faults (Yang et al, 2019;Yao & Yang, 2022).…”
Section: Model Configurationmentioning
confidence: 99%
See 3 more Smart Citations